Procedure for Establishing an Individual Limited Liability Company - Fauziah Agustini; Nursaiba Ritonga; Indah Purnama Sari; Devi Marsella Br Barus; Rifqa Khairunnisa (PT FORMOSA CENDEKIA GLOBAL, 2023)
In business world, many are experiencing quite a very rapid development. Many entrepreneurs choose individual limited liability company in running their business. The research method used is normative juridical which is qualitative in nature based on literature research. Data sources come from secondary data sources and tertiary data. The data was analyzed using a deductive mindset with a descriptive method and data analysis using a conceptual approach and a statute approach. Based on the results of the study, it was found that the concept of liability at PT Perorangan UMK is limited liability and protection for creditors against the risk of default by PT Perorangan UMK is through the enforcement of non-litigation and litigation legal remedies. The main conclusion is the importance of reviewing the risks that arise from the addition of Article 153J which has been amended in Article 109 of the Job Creation Law regarding the limitation of MSEs' liability which has not further regulated the protection of PT Perorangan UMK creditors.